INFANTILE CORTICAL HYPEROSTOSIS - Nika Morgan; Sara Bertok; Damjana Ključevšek; Karin Schara; Jana Lozar Krivec (The Society for Children with Metabolic Disorders, 2021)
Infantile cortical hyperostosis or Caffey disease is a rare genetic disorder caused by a mutation in the collagen 1 gene. The mechanism of the disease has not yet been fully elucidated, but the most important factor in the pathogenesis and the consequence of the mutation is periosteal inﬂammation. The disease becomes clinically evident during the ﬁrst months of life with asymmetrical bone thickening, most commonly in the mandible, clavicle, scapula, ribs, and long bones. Non-speciﬁc systemic inﬂammatory symptoms can also be present. X-ray imaging with demonstration of bone hyperostosis is essential for the diagnosis, which is conﬁrmed by genetic testing. Treatment is symptomatic. The prognosis of the disease depends on the mode of inheritance. The autosomal recessive form, known as the prenatal form, has a poor prognosis. The autosomal dominant form or infantile Caffey disease usually resolves spontaneously without consequences before the age of two years. We present a case of a neonate with Caffey disease with proven COL1A1 gene mutation.